2021
DOI: 10.1111/trf.16527
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the SARS‐CoV‐2 pandemic and civil unrest on massive transfusion protocol activations in Minneapolis 2020

Abstract: Background The year 2020 presented the transfusion community with unprecedented events and challenges, including the ongoing SARS‐CoV‐2 (COVID‐19) pandemic, and more recently by civil unrest, following the death of George Floyd in late May of 2020. As a level 1 trauma center located in Minneapolis, Minnesota, Hennepin Healthcare (HCMC) offers a unique perspective into the changes in massive transfusion protocol (MTP) activations and usage during this tumultuous period. This may provide insight for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…trauma-related MTP activations, including the patterns and length of community responses and measures taken to mitigate spread of the virus such as lockdowns and "stay-at-home" orders, variations in traffic patterns and accidental traumas, and general societal and geopolitical factors [20,21]. Interestingly, while many hospitals have struggled with blood shortages at different time-points throughout the pandemic, several respondents to our survey have not experienced blood shortages, or are just now beginning to face shortages.…”
Section: Discussionmentioning
confidence: 99%
“…trauma-related MTP activations, including the patterns and length of community responses and measures taken to mitigate spread of the virus such as lockdowns and "stay-at-home" orders, variations in traffic patterns and accidental traumas, and general societal and geopolitical factors [20,21]. Interestingly, while many hospitals have struggled with blood shortages at different time-points throughout the pandemic, several respondents to our survey have not experienced blood shortages, or are just now beginning to face shortages.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Braun et al reported that the number of MTP activations significantly increased because of violent trauma during the COVID‐19 pandemic in the United States of America [7]. In contrast, in our study population, most traumatic cases with an MTP trigger were due to motor vehicle ( n = 26, 56.5%) and falling ( n = 13, 28.3%) accidents, and no notable difference in traumatic cases with an MTP trigger was observed during the COVID‐19 outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in healthcare utilization combined with increased trauma activity and unprecedented rates of violence across the country depleted the available resources by an estimated 10% to 12% surplus usage. [1][2][3][4][5][6] The American Red Cross (ARC) and America's Blood Centers (ABC) have tried to alert the public to the ongoing need for blood donations. For example, the American Red Cross (ARC) released a statement in June of 2021:…”
mentioning
confidence: 99%
“…However, as the nation reopened and healthcare services resumed, a surge in blood consumption ensued. The increase in healthcare utilization combined with increased trauma activity and unprecedented rates of violence across the country depleted the available resources by an estimated 10% to 12% surplus usage 1–6 …”
mentioning
confidence: 99%